Security in wire/wireless networks: sniffing attacks prevention/detection techniques in LAN networks & the effect on biometric technology - Al-Hemairy, Moh'd Hussain (2010)
During the past era, Information Technology made a revolution in R&D. No double internet becomes an essential backbone of all sciences and research nowadays. Accordingly security threats and data banks attacks turn out to be a phenomenon. Thus, granting protection to such crucial information becomes a high demand. While reviewing the latest studies in this area, there are strong signs that attacking information warehouse is the hot topic nowadays. Moreover, preventing attacks to TCP/IP networks and what are the most efficient techniques to protect it, is the most targeted research area for security experts. For instance, what so called the Man-in-the-Middle attack [MiM] and denial of services [DoS] are just some ways of vulnerable attacks to TCP/IP networks, using some tools available free on the internet. They are sniffing the data traffic or causing service denial. In our research, we evaluated the most famous security solutions and classifying them according to their efficiency against detecting or preventing the types of Address Resolution Protocol [ARP] Spoofing attacks. Based on the surprising experimental results done by a previous study in the security lab which proposed an optimal algorithm to enhance their ability against the two famous network attacks; we implemented the proposed algorithm by this study and stimulate the experiment in order to test the algorithm performance. Moreover we studied the vulnerability of such attacks on two of the most famous security devices used for access-restricted sites; which is known as “Biometric devices”. The biometric technology includes fingerprint readers and Eye readers [iRIS scanners] and we’ll show how they are performing against network attacks.